The Redistributive Effect of Direct Taxes: An International Comparison of Six LIS Countries - John Bishop; Victor Chow; John Formby (Luxembourg Income Study (LIS), 1993)
Uses LIS microdata to construct Lorenz-type curves in order to make ordinal comparisons of tax two types of progressivity 'residual' and 'liability'. This analysis is applied to investigate the redistributive effect of direct taxes in six countries.
Keywords: 330